A feasibility study of using frac‐packed wells to produce natural gas from subsea gas hydrate resources. Issue 4 (18th December 2019) - Shan, Liqun; Fu, ChunKai; Liu, Yanchang; Qi, Yanyan
Abstract: Frac‐packing is an attractive technique to stimulate production for gas hydrate reservoirs with the additional benefit of solving the problematic sand production problems. So far, there have been no documented mathematical models to predict the propagation of fractures and to forecast gas production for frac‐packed gas wells. An analytical model was derived to predict the propagation of a horizontal fracture and to assess the well productivity in frac‐packed gas wells in a gas hydrate reservoir. The model assumes a steady, single‐gas, Darcy flow in the matrix and fracture. Case analyses were performed for key design and operational parameters with the analytical model. The result shows that it is easy to control the relationship between the wellbore fracturing pressure and injecting flow rate, and thus, fractures of any length can be produced in the fracture penetration process of frac‐packed wells. Case analysis also shows that the gas production rate increases nonlinearly with the fracture propagation and increases linearly with the fracture width. The increase in fracture width turns out to be surprisingly effective in improving well productivity without threshold within the investigated range of width. It was also found that the increase in fracture permeability contributes more to the productivity of the frac‐packed wells than the increase in matrix permeability. The model also assumes no flow at the boundary of the reservoir, which may underestimate those gas hydrate reservoirs with pressure supply. This work uses a theoretical approach to estimate the productivity of the frac‐packed gas hydrate reservoirs, which may benefit in solving the sand production issue during the production process as well. Abstract : An analytical model was derived to predict the propagation of a horizontal fracture in gas hydrate reservoirs. An analytical model for assessing the steady productivity in frac‐packed wells in gas hydrate reservoirs was developed. This work provides a practical way to address the sand production problem in harvesting natural gas from gas hydrate resources.